Worsened self-rated health in the course of the COVID-19 pandemic among older adults in Europe. - Lüdecke, Daniel; von dem Knesebeck, Olaf (European Journal of Public Health, 2023)
Background Governments across Europe deployed non-pharmaceutical interventions to mitigate the spread of coronavirus disease 2019 (COVID-19), which not only showed clear benefits but also had negative consequences on peoples' health. Health inequalities increased, disproportionally affecting people with higher age or lower education. This study analyzed associations between social factors and worsened self-rated health of elderly people in the course of the COVID-19 pandemic, taking different stringencies of government mandates as well as infection rates into account. Methods Data stem from the European SHARE survey. The main outcome was a binary indicator of worsened self-rated health. Analyses included data from two waves (2020 and 2021) during the pandemic (N  = 48 356 participants, N = 96 712 observations). Predictors were age, sex, education and living together with a partner, and two macro indicators that reflected the stringency of government response mandates and COVID-19 infection rates. Data were analyzed using logistic mixed-effects regression models. Results Older age [odds ratio (OR) 1.73, confidence interval (CI) 1.65–1.81] and female sex (OR 1.26, CI 1.20–1.32) were positively associated and higher education (OR 0.74, CI 0.70–0.79) was negatively associated with worsened self-rated health. Not living together with a partner showed higher odds of worsened self-rated health (OR 1.30, CI 1.24–1.36). Inequalities increased from 2020 to 2021. Associations between worsened self-rated health and government response mandates or infection rates were inconsistent. Conclusion Self-rated health worsened in the course of the pandemic and health disparities increased. Possible future pandemics require targeted interventions to minimize adverse health outcomes, in particular among old, potentially isolated, and deprived people.